Effect of Re content and support in the liquid phase conversion of furfural to furfuryl alcohol and 2-methyl furan over ReOx catalysts. (15th April 2019) - Toledo, F.; Ghampson, I.T.; Sepúlveda, C.; García, R.; Fierro, J.L.G.; Videla, A.; Serpell, R.; Escalona, N.
Graphical abstract: Highlights: Supported ReOx catalysts are active due to oxygen vacancies created by in situ partial reduction. The activity is linked to metal oxide-support interaction. The modest 2-MF selectivity (30%) over all solids was regardless to Re content and type of support. Lower hydrogen pressure and higher temperature favored the production of 2-methylfuran. Abstract: Supported rhenium oxide catalysts with different Re loadings (0.5–1.8 Re atom nm −2 ) and supports (SiO2, γ -Al2 O3 and SiO2 -Al2 O3 ) were tested for the liquid-phase conversion of furfural at 150–250 °C and 3–5 MPa H2 pressure. The reaction yielded furfural alcohol and 2-methylfuran as main products, the selectivity of which varied significantly with reaction temperature and H2 pressure. The reactivity of reducible rhenium oxide catalysts has been found to be associated with low-valent Re species formed by partial reduction of ReO4 − species by reactant hydrogen during the reaction. The formation of these sites is a strong function of the Re loading and the type of support used. In this study, activity based on the mass of the catalyst increased with Re content to a maximum value at 1.4 atoms of Re per nm 2 of support but then decreased at higher loading, consistent with loss of active sites due to aggregate formation. The product distribution was invariant to Re loading which is attributed to the nature of the active sites being identical regardless of Re content. In regards to support effect, the activity based on surface Re species increased in the order Al2 O3  < SiO2 -Al2 O3  < SiO2, which is consistent with ReOx -support interaction characteristics, and the reducibility of the catalysts. Minimal difference in products distribution was observed which indicates that support effects were less important for ReOx catalysts for the conversion of furfural.